2021
DOI: 10.1021/acs.energyfuels.0c04201
|View full text |Cite
|
Sign up to set email alerts
|

Stress Sensitivity for the Occurrence of Coalbed Gas Outbursts: A Reactive Force Field Molecular Dynamics Study

Abstract: Coalbed gas outburst processes commonly occur in ductile shear zones and release gas quantities that far exceed the maximum gas adsorption capacity of coal seams. Although outburst accidents pose a serious safety hazard, this process has long remained poorly understood at a molecular level. In this work, we use reactive force field molecular dynamics simulations to analyze the influence of stress on the mechanochemical decomposition reactions and products of coal macromolecular models. The results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As the coal deformation intensity increased, the value of A C / A Total gradually decreased (Figure ), indicating that tectonic stress could result in the dissociation of these functional groups. Further, simulative coal deformation experiments have shown that under the action of stress, oxygen functional groups (particularly carbonyl) can be dissociated into gases. It should be noted that the average A C / A Total values of scaly coals are lower than that of wrinkle coal, which indicates that higher shear stresses are likely to facilitate the disassociation of oxygen functional groups. Furthermore, the disassociation of oxygen functional groups can also break the hydrogen bonds connected with them, thereby increasing the motion and rearrangement of aromatic structures.…”
Section: Resultsmentioning
confidence: 99%
“…As the coal deformation intensity increased, the value of A C / A Total gradually decreased (Figure ), indicating that tectonic stress could result in the dissociation of these functional groups. Further, simulative coal deformation experiments have shown that under the action of stress, oxygen functional groups (particularly carbonyl) can be dissociated into gases. It should be noted that the average A C / A Total values of scaly coals are lower than that of wrinkle coal, which indicates that higher shear stresses are likely to facilitate the disassociation of oxygen functional groups. Furthermore, the disassociation of oxygen functional groups can also break the hydrogen bonds connected with them, thereby increasing the motion and rearrangement of aromatic structures.…”
Section: Resultsmentioning
confidence: 99%
“…A review by Lu et al presents a summary and perspective on efficient exploitation of CBM in China. The original research articles on this topic cover several aspects related to CBM, including gas adsorption, methane production, , numerical modeling and simulation, , pore-scale measurements, , characterization studies, , etc.…”
Section: Coalbed Methane (Cbm)mentioning
confidence: 99%
“…A review by Lu et al 62 presents a summary and perspective on efficient exploitation of CBM in China. The original research articles on this topic cover several aspects related to CBM, including gas adsorption, 63 methane production, 68,71 numerical modeling and simulation, 64,66 porescale measurements, 65,69 characterization studies, 67,70 etc. This VSI is part of the series of VSIs on recent advances in selected energy research areas, launched by Energy & Fuels in January 2021.…”
Section: ■ Coalbed Methane (Cbm)mentioning
confidence: 99%
“…A significant outburst of coal and gas accidents will be accompanied by energy release, which produces strong power in the period of underground mining. Gas outburst produces a large amount of pulverized coal, and the desorption gas of pulverized coal will further facilitate the outburst. Therefore, gas significantly influences the gestation and occurrence of gas outbursts. As coal mining depths increase, the amount and intensity of gas emissions also increase, which will induce more gas calamities. In addition to the high-intensity mining stage of deep coal seams, the coal has been strongly damaged many times during the coal-forming process, leading to the gas migration in the coal body and the circumstance of gas desorption–pulverization–desorption. , Consequently, studying the law of gas desorption in coal under damage conditions is crucial for understanding gas emission laws and gas flow mechanisms and predicting coal and gas outbursts. …”
Section: Introductionmentioning
confidence: 99%